Application of Service User Satisfaction Level of Service Quality at LPMP Using the Fuzzy Servqual Method - Shella Arsinta Fitri; Indra Kanedi; Eko Suryana (GATOTKACA Journal (Teknik Sipil, Informatika, Mesin dan Arsitektur), 2021)
Bengkulu Province Education Quality Assurance Institute has the duty to carry out quality assurance of basic and secondary education in the Province based on the policy of the Minister of Education and Culture. Every year, LPMP will hold training which is used to help improve the quality of teaching staff or supervisors. The data processing process at LPMP already uses a computerized system, one of which is the Office application. With this application, of course, it can make it easier for LPMP to evaluate the quality of services provided so far. The application of service user satisfaction level to service quality at LPMP using the Fuzzy Servqual Method is an application built to facilitate service users in providing value to the quality of services provided by LPMP and can also facilitate LPMP in evaluating service quality. In helping to analyze the level of service user satisfaction on service quality, this application has applied the Fuzzy Servqual Method. Application of service user satisfaction level to the service quality is made using Visual Basic .Net programming language and SQL Server 2008r2 database. Assessments are carried out every month, so service users cannot provide a rating in the same month. Based on the tests that have been carried out, the results show that the functionality of the application for the level of service user satisfaction on service quality at LPMP using the Fuzzy Servqual method runs as expected.